Clinical Outcome and Survival of Osteosarcoma Patients in Cipto Mangunkusumo Hospital: Limb Salvage Surgery versus Amputation - Achmad Fauzi Kamal; Heru Widyawarman; Kurniadi Husodo; Errol Untung Hutagalung; Wulyo Rajabto (Interna Publishing, 2016)
Aim: to analyze the outcome and survival rate of osteosarcoma patients in our hospital as well as the factors affecting prognosis and functional outcome. Methods: this is a retrospective cohort study of osteosarcoma patients in Cipto Mangunkusumo Hospital underwent limb salvage surgery (LSS), amputation, LSS + amputation, and refused surgery from year 1995 to 2014. The surgical decision was based on patient's age, staging, location, neurovascular involvement, Huvos type, functional demand, patient preference, and general condition. Functional outcome was assessed using the Musculoskeletal Tumor Society (MSTS) score with the maximum score of 30. Results: subjects consisted of 80 male and 52 female aged 4 to 61 year-old. They underwent limb salvage surgery (LSS) (n=37), amputation (n=42), LSS + amputation (n=2), and refused surgery (n=51). Overall 5-year cumulative survival rate was 14.6%. The 5-year survival rate for each group; LSS, amputation, combined LSS and amputation, and refused surgery was 34.8%; 15.9%; 0%; and 0%, respectively. Patients with tumor size <8 cm tend to underwent LSS compared to amputations (60.7% vs 39.3%, p=0.046). Local recurrence-free survival for LSS and amputation was 96.2% and 86.5% respectively (p=0.586). MSTS score was higher in LSS than amputation group (25.0 vs 18.5, p=0.011). Conclusion: LSS had higher survival rate than amputation in osteosarcoma patients who were treated in Cipto Mangunkusumo Hospital. MSTS functional score in the LSS group was higher than amputation group.